O discurso das professoras sobre as práticas de leitura na sala de aula do ensino fundamental - Cunha, Jussara Cristina da (2008)
It is in order to communicate that human beings create and use various forms of language. It is through them that the man was announced, has access to information, and advocates expressed views, sharing or build visions of world, produces knowledge. But to establish that communication, it is necessary that the parties give directions to the text (spoken or written), making it understandable. This is why we say that always involves reading comprehension, understanding that this is made in the interaction between reader and text. The concept of reading has changed significantly as the linguistic studies to be deepened. Currently, we approach a member of interacionista reading, in which this is seen as constant construction of directions from the interaction between speakers. However, despite this design have been crystallized in the academic environment, we do not yet know for sure how the teaching of reading and the construction of the meanings of the text happens in the classrooms of elementary school. Given this course, came the need to examine further how the teaching of reading is taught in the classrooms of classes from 1º to 5º of the year of elementary school. These reasons, that motivated this work, which aims to study of the speech and practice of ten teachers. To examine the discourse on teaching and learning, use of data research, conducted with the participation of those for teachers in the classroom. To examine the practice, develop a model questionnaire, containing 09 questions, according to the practical reality of the classroom of the interviewees. Based on the assumptions of Bakhtin, Piaget, Marcuschi, Kleiman, loved others, aim specifically investigate what has changed and what has not changed in the discourse and practice of teachers in terms of design, teaching, learning, reading and writing and what this practice shows for knowledge. We saw at the end of our analyses, that even with a recent theoretical training, the interviewees, still seem to work with the texts in the classroom from a perspective of reading purely structuralist.